Levofloxacin Population Pharmacokinetics in South African Children Treated for Multidrug-Resistant Tuberculosis - Denti, Paolo; Garcia-Prats, Anthony J; Draper, Heather R; Wiesner, Lubbe; Winckler, Jana; Thee, Stephanie; Dooley, Kelly E; Savic, Rada M; McIlleron, Helen M; Schaaf, H Simon; Hesseling, Anneke C (Antimicrobial agents and chemotherapy, 2018)
Levofloxacin is increasingly used in the treatment of multidrug-resistant tuberculosis (MDR-TB). There are limited pediatric pharmacokinetic data to inform dose selection for children. Children routinely receiving levofloxacin (250-mg adult tablets) for MDR-TB prophylaxis or disease in Cape Town, South Africa, underwent pharmacokinetic sampling following receipt of a dose of 15 or 20 mg/kg of body weight given as a whole or crushed tablet(s) orally or via a nasogastric tube. Pharmacokinetic parameters were estimated using nonlinear mixed-effects modeling. Model-based simulations were performed to estimate the doses across weight bands that would achieve adult exposures with 750-mg once-daily dosing. One hundred nine children were included. The median age was 2.1 years (range, 0.3 to 8.7 years), and the median weight was 12 kg (range, 6 to 22 kg). Levofloxacin followed 2-compartment kinetics with first-order elimination and absorption with a lag time. After inclusion of allometric scaling, the model characterized the age-driven maturation of clearance (CL), with the effect reaching 50% of that at maturity at about 2 months after birth and 100% of that at maturity by 2 years of age. CL in a typical child (weight, 12 kg; age, 2 years) was 4.7 liters/h. HIV infection reduced CL by 16%. By use of the adult 250-mg formulation, levofloxacin exposures were substantially lower than those reported in adults receiving a similar dose on a milligram-per-kilogram basis. To achieve adult-equivalent exposures at a 750-mg daily dose, higher levofloxacin pediatric doses of from 18 mg/kg/day for younger children with weights of 3 to 4 kg (due to immature clearance) to 40 mg/kg/day for older children may be required. The doses of levofloxacin currently recommended for the treatment of MDR-TB in children result in exposures considerably lower than those in adults. The effects of different formulations and formulation manipulation require further investigation. We recommend age- and weight-banded doses of 250-mg tablets of the adult formulation most likely to achieve target concentrations for prospective evaluation.